Safiyyah's war - Khan, Hiba Noor (Allida, an imprint of HarperCollins Publishers, 2024)
"War comes to the streets of Paris and Safiyyah's life changes for ever. Her best friend's family have fled, and the bombing makes her afraid to leave the mosque where she lives. But when her father is arrested by the Nazis for his secret Resistance work, it falls to Safiyyah to run the dangerous errands around the city. It's not long before hundreds of persecuted Jews seek sanctuary at the mosque. Can Safiyyah find the courage to enter the treacherous catacombs under Paris and lead the Jews to safety?"--Publisher's description